TERT Alterations Predict Tumor Progression in De Novo High-Grade Meningiomas Following Adjuvant Radiotherapy - Deng, Jiaojiao; Sun, Shuchen; Chen, Jiawei; Wang, Daijun; Cheng, Haixia; Chen, Hong; Xie, Qing; Hua, Lingyang; Gong, Ye (Frontiers in Oncology, 2021)
Background Adjuvant radiotherapy (RT) is one of the most commonly used treatments for de novo high-grade meningiomas (HGMs) after surgery, but genetic determinants of clinical benefit are poorly characterized. Objective We describe efforts to integrate clinical genomics to discover predictive biomarkers that would inform adjuvant treatment decisions in de novo HGMs. Methods We undertook a retrospective analysis of 37 patients with de novo HGMs following RT. Clinical hybrid capture-based sequencing assay covering 184 genes was performed in all cases. Associations between tumor clinical/genomic characteristics and RT response were assessed. Overall survival (OS) and progression-free survival (PFS) curves were plotted using the Kaplan–Meier method. Results Among the 172 HGMs from a single institution, 42 cases (37 WHO grade 2 meningiomas and five WHO grade 3 meningiomas) were identified as de novo HGMs following RT. Only TERT mutations [62.5% C228T; 25% C250T; 12.5% copy number amplification (CN amp.)] were significantly associated with tumor progression after postoperative RT (adjusted p = 0.003). Potential different somatic interactions between TERT and other tested genes were not identified. Furthermore, TERT alterations (TERT-alt) were the predictor of tumor progression (Fisher’s exact tests, p = 0.003) and were associated with decreased PFS (log-rank test, p = 0.0114) in de novo HGMs after RT. Conclusion Our findings suggest that TERT-alt is associated with tumor progression and poor outcome of newly diagnosed HGM patients after postoperative RT.